Electrochemical and reactions mechanisms in the minimization of toxic elements transfer from mine-wastes into the ecosystem. (20th August 2021) - Piervandi, Zeinab; Darban, Ahmad Khodadadi; Mousavi, Seyyed Mohammad; Abdollahy, Mahmoud; Asadollahfardi, Gholamreza; Dinelli, Enrico; Webster, Richard David; Funari, Valerio
Abstract: The generation of self-protective mine-wastes through a superficial secondary layer to prohibit the leaching of toxic elements can be a new perspective for future environmental studies. The bioleaching-based treatment can lead to the surface passivation of contaminated minerals, which inhibit trace elements mobility. In this work, the electrochemical and passivation mechanisms for the minimization of mine-wastes dissolution were studied on a laboratory scale. The electrochemical behavior of bio-treated soil during surface passivation was investigated by cyclic voltammetry (CV) analysis. The concentration of Fe 2+ and Fe 3+ in bio-treatment leachates was analyzed to improve our knowledge about the competitive effect of iron ions on the chemical and bacterial dissolution of sulfide tailings. The results of transmission electron microscopy (TEM) and electron probe micro-analyzer (EPMA) confirmed the surface coating of metal sulfides, which led to approximately complete passivation of the minerals. The CV analysis represented that the passivation layer produced in the presence of Acidithiobacillus bacteria was stable in a wide range of redox potential. This study showed that Fe 3+ ions play a controlling role in the dissolution process. The high concentration of ferric ions generates a passivation layer in the bulk solution of (bio)leaching. The kinetics study of copper mobility in the minimization process conformed to diffusion control. The results of the kinetics analysis showed that the Cr bioleaching mechanisms followed both the chemical model and diffusion model. Graphical abstract: Image, graphical abstract